Qualidade de vida e função sexual de mulheres com dor pélvica - Luz, Rosa Azevedo da (2018)
Objectives: To compare the quality of life (QoL) and sexual function of women with and without chronic pelvic pain and to investigate factors associated with QoL and sexual dysfunction in women with chronic pelvic pain. Methods: A cross-sectional study conducted between October 2014 and February 2016 at the gynecology outpatient clinic of the Federal University of Goiás Teaching Hospital, Goiânia, Goiás, Brazil evaluated 200 women, 100 with and 100 without chronic pelvic pain. Sociodemographic, clinical and behavioral characteristics were investigated. Pain intensity was measured using a visual analogue scale. QoL was evaluated using the World Health Organization’s short-form WHOQOL-BREF questionnaire, and the Female Sexual Function Index was used to evaluate sexual function. Anxiety and depression were investigated using the Hospital Anxiety and Depression Scale. Student’s ttest, the chi-square test and the Mann-Whitney test were used to compare sociodemographic, clinical and behavioral characteristics between the groups. A generalized linear model was used to compare QoL and sexual function scores between the groups and to identify factors associated with QoL in the women with chronic pelvic pain. Multiple logistic regression analysis was used to identify factors associated with sexual dysfunction in women with chronic pelvic pain. Results: The mean age of the participants with chronic pelvic pain was 37.8 ± 8.0 years compared to 37.2 ± 9.6 years for those without this condition (p=0.648). Analysis adjusted for potential confounding factors showed that women with chronic pelvic pain had significantly lower QoL scores for the physical health (p<0.001) and social relationships (p=0.025) domains. Anxiety, depression, pain intensity, diabetes mellitus, arterial hypertension, sexual dysfunction, lower monthly income and marital status (not having a partner) were factors found to be negatively associated with QoL. Employment status (being employed/in paid work), parity (≥ 1) and menopausal status (postmenopausal) were positively associated with QoL. The prevalence of sexual dysfunction was 81% in the women with chronic pelvic pain and 58% in those without it (p=0.003). Women with chronic pelvic pain had significantly lower scores in the desire (p=0.038), arousal (p=0.002), lubrication (p=0.011), orgasm (p<0.002) and pain (p<0.001) domains. There were no statistically significant differences with respect to the satisfaction domain or the overall score. Depression was the only factor found to be positively and independently associated with sexual dysfunction in women with chronic pelvic pain (p=0.012). Conclusions: QoL was poorer in the group of women with chronic pelvic pain, with various factors being negatively associated with QoL in this group. Sexual dysfunction was also more common in the group with chronic pelvic pain, with these women scoring lower in most of the sexual function domains. Depression was positively associated with sexual dysfunction in the chronic pelvic pain group. These findings highlight the need to take into consideration the influence of various different factors that affect the QoL of women with chronic pelvic pain. Furthermore, these results suggest that women with chronic pelvic pain should be routinely screened for sexual dysfunction, taking into account the effect of psychological factors.